Cleft Lip and Palate Treatment A Comprehensive Guide (Springer International Publishing, 2018)
The aim of this book is to discuss cleft lip and palate deformities in a comprehensive way, presenting it from the basics to the most clinically and surgically relevant issues. First, the basic concepts of embryology and pathogenesis of the facial deformities will be discussed. Special attention will be paid to the genetics underlying this condition. Following that, basic principles of surgical treatment through the most recent advances in the field will be presented, along with most important evidences from the literature and the personal experience of the editors and authors. Cleft Lip and Palate Treatment presents the state of the art and advances in the field and is intended to serve as a comprehensive guide for a broad audience. All the specialties involved in the comprehensive care of these craniofacial deformities will be presented in this book.